Impact of Tenofovir Disoproxil‐Induced Fanconi Syndrome on Bone Material Quality: A Case Report. (25th May 2021) - Hadzimuratovic, Benjamin; Haschka, Judith; Hartmann, Markus A; Blouin, Stéphane; Fratzl‐Zelman, Nadja; Zwerina, Jochen; Kocijan, Roland
ABSTRACT: Tenofovir is a nucleotide analog reverse‐transcriptase inhibitor (NtARTI) used for treatment of chronic hepatitis B and human immunodeficiency virus (HIV). Fanconi syndrome (FS) is a condition affecting the proximal tubules of the kidney, leading to increased passage and impaired reabsorption of various small molecules such as glucose, phosphate, bicarbonate, and amino acids. Tenofovir disoproxil fumarate (TDF) is one of two pro‐drugs of tenofovir associated with a greater nephrotoxicity and renal complications such as FS with subsequent osteomalacia, acute kidney injury, and reduction of glomerular filtration rate (GFR) compared with tenofovir alafenamide (TAF). We present the case of a 33‐year‐old white woman treated with TDF because of chronic hepatitis B infection suffering four atraumatic fractures over the period of 2 years. The patient was taken off the TDF regimen 3 months before presentation. Initial blood and urine samples suggested the presence of TDF‐induced osteomalacia, which was confirmed by transiliac bone biopsy and histomorphometry. Moreover, bone mineral density distribution (BMDD) by quantitative backscattered electron imaging (qBEI) analysis showed that approximately 56% of the bone surface was normally mineralized and 44% showed a reduced mineralization consistent with the presence of osteomalacia. The patient made a significant recovery upon cessation of the causative agent. This case report emphasizes the use of bone biopsy, histomorphometry and qBEI in confirming the diagnosis of drug‐induced Fanconi syndrome and associated osteomalacia. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.